THE EFFECT OF DIFFERENT DOSES OF GROTOP BOSTER FEEDING IN FEED ON THE GROWTH AND SURVIVAL RATE OF FRESHWATER POMFRET FISH (Colossoma macropomum) IN THE RECIRCULATION SYSTEM - Dicky Januandri Silalahi; Iskandar Putra; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRAK This study aims to obtain the best dose of grotop booster for the growth and survival of freshwater pomfret (Colossoma macropomum) in a recirculation system. This research was conducted in November-December 2020 at the Aquaculture Technology Laboratory, Faculty of Fisheries and Marine Affairs, Riau University. This study used a completely randomized design (CRD) with 5 treatment levels and 3 replications. P0 (Without giving grotop booster), P1 (Grotop booster dose 25 g/kg feed), P2 (Grotop booster dose 30 g/kg feed), P3 (Grotop booster dose 35 g/kg feed), P4 (Grotop booster dose 40 g/kg feed). Freshwater pomfret fish (Colossoma macropomum) used measuring 5-7 cm as many as 150 fish with a stocking density of 10 fish/cm3 and kept in an aquarium measuring (60 x 40 x 40) cm3. The results showed that giving grotop booster with different doses had a significant effect (P<0.05) on protease enzyme activity, absolute weight growth, absolute length growth, specific growth rate, survival rate, and feed conversion. The results showed that the best grotop booster was given at a dose of 40 g/kg feed, which resulted in protease enzyme activity (0.1718 IU/mL), absolute weight growth (5.85 g), absolute length growth (3.65 cm). , specific growth rate (4.08%), feed efficiency (80.34%), feed conversion (1.24), and survival rate (100%). Key words : Freshwater Pomfret, Grotop booster, Growth